The effects of vertical integration on oil company performance - Barrera-Rey, F (Oxford Institute for Energy Studies, 1995)
When asked to rank industries by their degree of vertical integration, most people would agree that the oil industry should come top of the list. Underlying this belief is the fact that integration and size tend to be closely associated. As the oil industry is so large and oil companies so visible and perceived as so profitable, the common belief is a correlation between vertical integration, size and performance. If a dynamic view is taken of this cross-sectional observation we would expect to find an oil industry populated only by fully integrated very large companies. However, a closer look at the industry shows a large dispersion in the segments in which companies participate, and even companies in the same segments use the market in different degrees. Furthermore, the average degree of integration of the industry does not exhibit a specific trend over time. The only periods when trends are seen are periods of either large uncertainty (the intra-war periods) or large market power (the period of existence of the Standard Oil Trust). Although the public and the government agencies may have a view of the large advantages of integration, the surprising fact is that many empirical studies do not focus on its costs. The observation of dispersion and stability of integration would suggest, as theoretical studies do, that a cost-benefit analysis of integration is needed. This study uses that driving hypothesis and tests for the costs and benefits of integration. The measure of costs of integration should reflect the effects of slack, diseconomies of size and diseconomies of diversification. The obvious choice is a measure of efficiency, namely technical efficiency, that looks at waste assuming inputs are used in the right proportion. The advantages of integration are traditionally set in terms of reliable supply of inputs or reliable demand for outputs. As the existence of uncertainty is a feature of oil markets, a test of uncertainty is made in the form of variability of efficiency. The use of efficiency in both tests is made for the purpose of consistency and is incorporated in the same econometric framework. The cost-benefit analysis would suggest that each company pursues integration Lip to the point where its benefits are outweighed by its costs. The results in this paper confirm just that: vertical integration reduces the level of efficiency of companies while it also reduces its variability. In other words, there are diseconomies of diversification but the market also incorporates inefficient volatility. However, the results are not impervious to change, there are periods when the inefficiency associated with integration is smaller as is also the risk-reducing ability of the strategy. This may help to explain the reasons why different degrees of integration may be optimal.